2001
DOI: 10.1200/jco.2001.19.6.1818
|View full text |Cite
|
Sign up to set email alerts
|

Localized Ewing Tumor of Bone: Final Results of the Cooperative Ewing’s Sarcoma Study CESS 86

Abstract: Fifty-two percent of CESS 86 patients survived after risk-adapted therapy. High-risk patients seem to have benefited from intensified treatment that incorporated ifosfamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
223
5
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(251 citation statements)
references
References 38 publications
14
223
5
9
Order By: Relevance
“…[27][28][29] It has been well confirmed that ESFT patients with larger tumors have a poorer outcome. 6,17,27,29,30 However, recent studies have demonstrated that this classic prognostic factor may become less critical when it is accompanied by the application of more aggressive treatment, such as EW-92, 25 SE 91-CNR, 9 and P6 8 (see Table 1). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[27][28][29] It has been well confirmed that ESFT patients with larger tumors have a poorer outcome. 6,17,27,29,30 However, recent studies have demonstrated that this classic prognostic factor may become less critical when it is accompanied by the application of more aggressive treatment, such as EW-92, 25 SE 91-CNR, 9 and P6 8 (see Table 1). …”
Section: Discussionmentioning
confidence: 99%
“…Although the histologic response to initial chemotherapy was among the most reliable predictive factors, 16,17,28,31,32 even with the limitation that tumors had to be resected to determine response, we also used simple radiographic evaluations based on changes in extraosseous tumor size. These evaluations also demonstrated sufficient predictive value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors involved in the prognosis include site of the tumor, tumor volume, age, sex, resection rate of tumor, presence of metastasis, treatment response, anemia, fever, and an increase in LDH [13][14][15]. For 20 years, the gold standard in the treatment of Ewing sarcoma of the limb is the combination of neo-adjuvant chemotherapy and enbloc resection.…”
Section: Discussionmentioning
confidence: 99%
“…An EFS of 70% was achieved for patients with localized disease, and OS reached 80%. [4][5][6][7][8][17][18][19][20][21] The outcome of metastatic patients remains dismal, especially for patients with bone and BM involvement. [4][5][6][9][10][11] Rodriguez Galindo et al 23 suggested risk stratification, taking into account simple clinical features, such as age, stage, tumor volume, localization and histological response to chemotherapy, to modulate treatment intensification in different subgroups.…”
Section: Discussionmentioning
confidence: 99%